Divine and demonic in the poetic mythology of the Zohar: the "other side" of Kabbalah - Berman, Nathaniel (IJS studies in Judaica, 2018)
Front Matter -- Copyright page -- Dedication -- Prefatory Note: Bibliography, Footnotes, Principal Texts, Translations, and Transliterations -- Acknowledgements -- Introduction: Poetic Mythology for a Broken World -- Demonic Writing: the Rhetoric and Ontology of Ambivalence -- A Divided Cosmos -- The Formation of Self and Other through Abjection and Crystallization -- Impersonating the Self, Collapsing into the Abyss: the Convergence of Horror and Redemption -- Conclusion: the Divine/Dunghill, or, the Self Is the Other -- Back Matter -- Bibliography -- Index.